2015
DOI: 10.1039/c5tb00608b
|View full text |Cite
|
Sign up to set email alerts
|

Stability, cytotoxicity and cell uptake of water-soluble dendron–conjugated gold nanoparticles with 3, 12 and 17 nm cores

Abstract: This article describes the synthesis of water-soluble dendron-conjugated gold nanoparticles (Den-AuNPs) with various average core sizes and the evaluation of stability, cytotoxicity, cell permeability and uptake of these materials. The characterization of Den-AuNPs using various instruments including transmission electron microscopy (TEM), matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF-MS), 1H NMR, FT-IR, and UV-vis spectroscopy confirms the dendron conjugation to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…In general, the UCNPs@SiO 2 , owing to the silica shell, were found to be hydrophilic, required for live cell applications, and nontoxic to the cells as compared with metallic NPs reported in the literature. Deol et al showed the cytotoxicity of ≈9 ppm of AuNPs, with approximately the same size as these UCNPs@SiO 2, to be considerably high in 3T3 cells with a viability of only 60% . In hepatic stellate cells (HSCs) apoptosis increased to 80% with the application of 250 ppm of silver NPs independent of their size from 10 to 50 nm .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the UCNPs@SiO 2 , owing to the silica shell, were found to be hydrophilic, required for live cell applications, and nontoxic to the cells as compared with metallic NPs reported in the literature. Deol et al showed the cytotoxicity of ≈9 ppm of AuNPs, with approximately the same size as these UCNPs@SiO 2, to be considerably high in 3T3 cells with a viability of only 60% . In hepatic stellate cells (HSCs) apoptosis increased to 80% with the application of 250 ppm of silver NPs independent of their size from 10 to 50 nm .…”
Section: Resultsmentioning
confidence: 99%
“…Deol et al showed the cytotoxicity of ≈9 ppm of AuNPs, with approximately the same size as these UCNPs@SiO 2, to be considerably high in 3T3 cells with a viability of only 60%. [31] In hepatic stellate cells (HSCs) apoptosis increased to 80% with the application of 250 ppm of silver NPs independent of their size from 10 to 50 nm. [32] 500 × 10 −6 m of cobalt (Co) NPs incubated for 24 and 48 h in BRL-3A (liver) cells were also found to reduce cell viability to <30, and <20% respectively.…”
Section: Supportingmentioning
confidence: 99%
“…As expected, the functionalization of gold-coated nanoparticles with dendrons prevent aggregation in biological fluids in broad spectrum of pH, in contrast to non-functionalized AuNPs irreversibly aggregated in acidic pH. Additionally, the presence of large dendron ligands protect nanoparticles core from the ionic disruptions resulting in their good stability and solubility in the aqueous solution with the salt concentration of up to 100 mM [ 143 ]. There is also urgent need to improve biodistribution of paclitaxel, whose great antineoplastic properties are limited due to its insolubility in aqueous media and acquired cells chemoresistance.…”
Section: The Employment Of Nanoformulations To Modulate Pharmacokinetmentioning
confidence: 77%
“…Conducted studies confirmed that drugs encapsulation into nanoemulsion results in good stability, longer drugs circulation in blood, lower clearance and metabolism followed by higher accumulation in cancer tissues [ 63 ]. Deol et al engaged FDA-approved, low toxic and non-immunogenic dendrimers to design water-soluble dendron–conjugated gold nanoparticles (Den-AuNPs) in order to improve stability of AuNPs in water solutions [ 143 ]. Despite having the significant anti-cancer potential, the medical use of gold-based nanotherapeutics is expressively reduced due to poor biocompatibility of these structures determined by low colloidal stability required for the prevention of AuNPs agglomeration under physiological conditions [ 144 ].…”
Section: The Employment Of Nanoformulations To Modulate Pharmacokinetmentioning
confidence: 99%
“…Detailed information regarding materials, synthetic procedures, and characterizations ( 1 H NMR, FT-IR, and TGA) for glutathione-capped gold nanoparticles (gAuNP) [2831], cetyltrimethylammonium bromide (CTAB)-capped gold nanoparticles (cAuNP) [9], and CTAB-capped gold nanorods (cAuNR) [9], and instrumental methods used to conduct the research presented in this article are provided in the previous publications and Additional file 1 [15, 24, 29].…”
Section: Experimentalsmentioning
confidence: 99%